The 13-story treehouse - Griffiths, Andy, 1961-; Denton, Terry (New York : Feiwel and Friends, 2013)
Who wouldn't want to live in a treehouse? Especially a 13-story treehouse that has a bowling alley, a see-through swimming pool, a tank full of sharks, a library full of comics, a secret underground laboratory, a games room, self-making beds, vines you can swing on, a vegetable vaporiser and a marshmallow machine that follows you around and automatically shoots your favourite flavoured marshmallows into your mouth whenever it discerns you're hungry. Life would be perfect for Andy and Terry if it wasn't for the fact that they have to write their next book, which is almost impossible because there are just so many distractions, including thirteen flying cats, giant bananas, mermaids, a sea monsters pretending to be mermaids, enormous gorillas, and dangerous burp gas-bubblegum bubbles!
"Orginally published as The 13-storey treehouse in Australia by Pan Macmillan Australia Pty Ltd."
Keywords: Books and reading -- Juvenile fiction; Tree houses -- Juvenile fiction